Handbook of smoke control engineering - Klote, John H.; Milke, J. A.; Turnbull, Paul G., 1961- (American Society of Heating, Refrigerating and Air-Conditioning Engineers, 2012)
"In handbook form to be useful to practicing engineers and other professionals, this book addresses smoke control design, smoke management, controls, fire and smoke control in transport tunnels, and full scale fire testing. For those getting started with computer models CONTAM and CFAST, there are simplified instructions with examples"--